2018
DOI: 10.1007/s00383-018-4312-7
|View full text |Cite
|
Sign up to set email alerts
|

Serial intralesional triamcinolone acetonide injections for acquired subglottic stenosis in premature infants

Abstract: Serial intralesional steroid injections are likely to be effective in improving the patency of acquired SGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[7][8][9] Steroid injections have also been utilized to decrease inflammation at the surgical site. [7][8][9]15 However, if inflammation and edema contributing to poor healing at the surgical site persists despite these interventions, other methods will need to be considered. In this case, we used a steroid-eluting implant in a pediatric patient with persistent granulation tissue, edema, and stenosis after dsLTR.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Steroid injections have also been utilized to decrease inflammation at the surgical site. [7][8][9]15 However, if inflammation and edema contributing to poor healing at the surgical site persists despite these interventions, other methods will need to be considered. In this case, we used a steroid-eluting implant in a pediatric patient with persistent granulation tissue, edema, and stenosis after dsLTR.…”
Section: Discussionmentioning
confidence: 99%
“…9 Sekioka et al found that serial triamcinolone acetide injections in infants with ASGS led to improvements in the patency of the subglottis. 10 However, not all studies have found post-injury steroids to be efficacious. In a canine model, Doolin et al found no change in collagen formation after subglottic injury with oral dexamethasone compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the role of adjuvant therapies, such as topical agents or intralesional injections, remains nebulous. 3,5,14,15 Ciprodex solution (ciprofloxacin-dexamethasone; Novartis Pharmaceuticals Corporation) has been noted to decrease edema and granulation tissue in the airway 14,16 and is routinely applied by some surgeons after balloon dilation; however, reports of its efficacy are largely anecdotal. 4,14 Given the lack of clarity regarding these variables, use of an animal model is an appropriate means for further investigation, and our group has described a method for reliably producing subglottic stenosis in a live rabbit model.…”
mentioning
confidence: 99%
“…There is a theoretical risk that prolonged occlusion of the airway can lead to cardiopulmonary effects due to negative intrathoracic pressure or direct vagal stimulation, although a paucity of data on this subject exists in the medical literature. Likewise, the role of adjuvant therapies, such as topical agents or intralesional injections, remains nebulous 3,5,14,15 . Ciprodex solution (ciprofloxacin‐dexamethasone; Novartis Pharmaceuticals Corporation) has been noted to decrease edema and granulation tissue in the airway 14 , 16 and is routinely applied by some surgeons after balloon dilation; however, reports of its efficacy are largely anecdotal 4 , 14 .…”
mentioning
confidence: 99%